A multi‐center, multinational age‐ and gender‐adjusted normative dataset for immunofluorescent intraepidermal nerve fiber density at the distal leg. (23rd October 2015) - Provitera, V.; Gibbons, C. H.; Wendelschafer‐Crabb, G.; Donadio, V.; Vitale, D. F.; Stancanelli, A.; Caporaso, G.; Liguori, R.; Wang, N.; Santoro, L.; Kennedy, W. R.; Nolano, M.
Abstract : Background and purpose: Quantification of intraepidermal nerve fibers (IENFs) in skin biopsies is now the tool of choice to diagnose small fiber neuropathies. An adequate normative dataset, necessary to assess normality cutoffs, is available for brightfield microscopy but not for immunofluorescence. Methods: Intraepidermal nerve fiber density data in distal leg skin samples processed with immunofluorescence were collected from 528 healthy individuals from four experienced laboratories worldwide. In all laboratories skin samples were collected, processed and analyzed according to standard procedures. Quantile regression analysis was employed to tailor the fit of the 5° percentile as the normal cutoff value and to test and measure the effect of age, gender, body mass index, race, biopsy site (lateral distal lower leg or medial posterior mid‐calf) and participating laboratory as possible influential variables. Results: Age, gender and biopsy site showed an independent linear correlation with IENF density. For each decade the 5° quantile IENF cutoff showed a 0.54 fibers/mm decrease, whilst females exhibited a 1.0 fiber/mm cutoff greater than males. Compared to the lateral distal lower leg, biopsies from the calf showed a 3.4 fibers/mm lower 5° percentile cutoff, documenting a variation linked by site. Conclusions: An age‐ and gender‐adjusted normative dataset for IENF density at the lateral distal lower leg obtained with indirect immunofluorescence is presented for the first time by sharing data from four experienced laboratories worldwide. This dataset can be used as reference for laboratories processing skin biopsies with this technique.